Temel Gazetecilik Kavramlar, Teknikler, Yenilikler - Şentöregil, Merve; Yılmaz, Elif; Atay, Tülây; Karaduman, Murad; Duru, Muhammet Erdem; Ghadiani, Esin; Göçer, Ferhat; Durgeç, Petek; Ünlü Karataş, Nagihan; Akyüz Ertunç, Elif; Sarı, Ergin; Topsakal, Taybe; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-